Analysis of Factors Related to Exclusive Breastfeeding During The Covid-19 Pandemic - Istisya, Afifah Salsabilla; Simanjuntak, Betty Yosephin; Marleni, Wisuda Andeka (Jurnal Kesehatan Prima, 2022)
Exclusive breastfeeding during the Covid-19 period should ideally continue by implementing health protocols that ensure sufficient breast milk for babies during the Covid-19 pandemic to form antibodies to the baby's immune system against Covid-19 virus infection. The purpose of this study was to determine the factors associated with the success of exclusive breastfeeding during the Covid-19 pandemic at Karang Tinggi Health Center. The factors studied were exposure to information, mother's knowledge, maternal anxiety, support from health workers and the application of health protocols and the success of exclusive breastfeeding. This study uses a descriptive analysis and a cross sectional approach by distributing questions in an online questionnaire about breastfeeding during the Covid-19 pandemic. The sample amounted to 82 samples. Sampling using total sampling technique. Analyzed through chi-square statistical test followed by logistic regression test. The percentage of mothers who gave exclusive breastfeeding during the Covid-19 pandemic at the Karang Tinggi Health Center was 41.5%. There is a significant relationship between information exposure and exclusive breastfeeding during the Covid-19 pandemic with p-value = 0.017. There is a significant relationship between knowledge of breastfeeding mothers and exclusive breastfeeding during the Covid-19 pandemic with p-value = 0.003. There is a significant relationship between the anxiety of breastfeeding mothers and exclusive breastfeeding during the Covid-19 pandemic with p-value = 0.028. There is a significant relationship between the support of health workers and exclusive breastfeeding during the Covid-19 pandemic with p-value = 0.020. There is a significant relationship between the implementation of health protocols and exclusive breastfeeding with p-value = 0.033. The most dominant factor related to exclusive breastfeeding was the support of health workers p=(0.08); OR= 5.087 Health workers need to motivate and provide counseling to breastfeeding mothers to increase exclusive breastfeeding.